Can a communication assessment provide a reliable indication of a child’s communication at interview? - Smethurst, Alex Jane (Psychology, crime & law, 2022)
Criminal justice systems rely heavily upon spoken language. This presents significant barriers for young witnesses who may have difficulty putting their experiences into words. In order to give their best evidence these witnesses may require additional scaffolding during an investigative interview. The current study is the first to examine the efficacy of ‘Unpacking the Box’ – a tool used by police officers and intermediaries to assess children’s communication abilities and determine the nature of scaffolding required. The study involved children, aged four to nine, taking part in a staged event. The children were allocated to one of three experimental conditions (assessment, no assessment, colouring). One week later, the children were interviewed about their experiences. Prior to the interviews, predictions were made regarding the children’s interview performance. The predictions for the children in the assessment condition were based on the findings of an ‘Unpacking the Box’ assessment. As for the children in the other conditions the predictions were based on professional judgement. The analysis looked at how closely the predictions reflected the children’s interview performance. Communication assessments were found to be superior to professional judgement in ascertaining a child’s abilities; thus, enabling interviewers to conduct more effective interviews with children.